2001
DOI: 10.1038/89901
|View full text |Cite
|
Sign up to set email alerts
|

Replication-selective virotherapy for cancer: Biological principles, risk management and future directions

Abstract: In the search for novel cancer therapies that can be used in conjunction with existing treatments, one promising area of research is the use of viral vectors and whole viruses. This review describes the underlying biological principles and current status of the field, outlines approaches for improving clinical effectiveness and discusses the unique safety and regulatory issues surrounding viral therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
340
0
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 457 publications
(350 citation statements)
references
References 57 publications
5
340
0
5
Order By: Relevance
“…11 In clinical trials, the response rate for tumors in patients treated with combinations improved compared to tumors in patients treated with chemotherapy alone. 13 There are several possible mechanisms underlying the synergy between virotherapy and chemotherapy. We have observed that Ad downregulates the expression of multidrug-resistant proteins like MRP in vitro (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 In clinical trials, the response rate for tumors in patients treated with combinations improved compared to tumors in patients treated with chemotherapy alone. 13 There are several possible mechanisms underlying the synergy between virotherapy and chemotherapy. We have observed that Ad downregulates the expression of multidrug-resistant proteins like MRP in vitro (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…2,[6][7][8][9] Clinical trial data also suggest the utility of oncolytic Ads for the treatment of cancer. [10][11][12][13][14] Previously, we described the oncolytic Ad called Ar6pAE2fF, in which the E2F-1 promoter controls expression of E1A. 4 This oncolytic Ad was safe and efficacious when delivered intratumorally.…”
mentioning
confidence: 99%
“…Other human DNA viruses have been used to kill tumor cells (for a recent review of this topic, please see Kirn et al 65 ). The E1b-mutant adenovirus ONYX-015 was recently shown in clinical trials to have antitumor activity, especially when administered in combination with chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…1 As the g 1 34.5 gene is responsible for the neurovirulence of HSV-1, g 1 34.5 gene-deficient mutants are considered to be useful as vectors for oncolytic therapy. 2,3 However, it was reported that they exerted only limited antitumor activity on their own.…”
Section: Introductionmentioning
confidence: 99%